Bunching system based on the evanescent waves - Ayzatsky, M.I.; Kramarenko, K.Yu.; Perezhogin, S.A. (Вопросы атомной науки и техники, 2001)
To improve the beam bunching at the initial stage of acceleration it is necessary to create an increasing field distribution. Such distribution can be created in the ordinary disk-loaded waveguide in its stopbands. Generally, there are two eigen evanescent waves, one of which has increasing distribution along the longitudinal axes and another - decreasing one. The field structure in the bounded system is a superposition of these two evanescent waves whose amplitudes are determined by the operating frequency and by the geometry of the boundary cavities. The results of the simulation of the buncher for the case of the 25 keV injected electron energy are presented in the paper.